Proceso de atención de enfermería a un paciente pediátrico con absceso perianal - Mendoza Carriel, Yosenka Lisbeth (2019)
Perianal Abscess is an infection characterized by a collection of pus, which forms under the skin within the soft tissue just around the anus, relatively common in children, frequently occurs in male infants under 1 year of age, although it can occur in any sex and age. The objective of this clinical case is to apply the Nursing Care Process to a pediatric patient with a medical diagnosis of Perianal Abscess, hospitalized in the area of Pediatrics of the Sacred Heart of Jesus Basic Hospital. Thanks to this case we were able to determine that the Nursing Care Process is essential to provide quality care and warmth to pediatric patients with Perianal Abscess, helping to improve their sanitary conditions and considerably improving clinical manifestations, being the most important for the early recovery, medical treatment and nursing interventions executed.